IMPLEMENTASI PERATURAN MENTERI DESA PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI NOMOR 8 TAHUN 2016 TENTANG PERUBAHAN ATAS PERATURAN MENTERI DESA PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI (Journal Ilmu Sosial, Politik dan Pemerintahan, 2017)
This study aimed to describe and analyze: (1)Implementation of Regulation of Minister of VillagesUnderdeveloped Regions and Transmigration Number 8 Year 2016 on Priority Fulfillment Usage of Village Fund in Pinang Tunggal Village.(2) Supporting and Inhibiting Factors of Implementation of regulation of Minister of Villages Underdeveloped Regions and Transmigration Number 8 Year 2016 On Priority Fulfillment Usage of Village Fund in Pinang Tunggal Village.Indicators in determining the success of implementation by using the Implementation Model by George C. Edward include: Communication, Resources, Disposition and Bureaucracy Structure.In this study the author used descriptive qualitative research methods.While the data collection was done through observation, interviews and documentation.Data source from this study used the informant namely Village Head, Village Secretary, Head of Government Affairs, Head of Development Affairs, Chairman of BPD, Head of LPMD, Head of Neighbourhood I and II, and Community of Pinang Tunggal Village.The results of this study indicated that the Implementation of Regulation of the Minister of Villages Underdeveloped Regions and Transmigration No. 8 of 2016 on the Priority Fulfillment Usage of Village Fund Year 2016 has not been implemented by Government of Pinang Tunggal Village.This was based on (1) the lack of communication in the process of prioritizing the use of the Village Fund, the low quality of human resources so that the responses to implement the regulation seem indifferent, less effective coordination shown by village government, BPD, and elements of society so that the priority of the the village fund was decided unilaterally by the village government.(2) Supporting factors, adequate budgets of village funds, priority programs/ activities have implications for the needs of the community.Inhibiting factors, village governments were dominantly closed and self-employed, such as in determining the priority of Village fund conducted unilaterally by the Village Government, the lack of disposition to implement the regulation of minister of villages (Permendesa) so as to appear indifferent to the regulation.(3) Suggestion, hopefully in the future, the regulation47of minister of villages(Permendesa) in determining the priority of the use of Village Fund can be implemented by Pinang Tunggal Village Government